(untitled) (Proceedings of the North American Academy of Liturgy, 2025)
This Berakah Award Response seeks to challenge understandings of Christian worship that have constricted the understanding of who belongs to the worshipping assembly in starkly anthropocentric ways. Instead, the Address encourages a return to an earlier, truly cosmic understanding of worship, rooted in God's primordial act of creation.